The effect of example and non-example learning model on fourth- grade students’ critical thinking skills on civic education - Nurunissa, Amelia Lutfian; Abdullah, Kusmajid (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2023)
This study aims to determine the effect of using Example and Non- Example models on students' critical thinking skills. The research location is one of the elementary schools in South Jakarta, to be precise at the fourth-grade level during the even semester of the 2021/2022 academic year, especially in the Civic Education subject. While the research method used is a quantitative research method with a Quasi-Experimental Design research design. The sampling technique used probability sampling on students who already understood Civic Education subjects by looking at their average scores in the previous semester, the number of subjects was 63 participants, with 31 participants grouped into the experimental group and 32 participants grouped into the control group. The data were obtained by distributing questionnaires to research subjects using multiple choice and filling methods, and the data that had been collected showed the results of the t test calculation of t count = 5.47 ≥ t table = 2.00 which stated that there was a significant effect, in student learning outcomes in the application of the Example and Non-Example models to improve students' critical thinking in the Citizenship Education subject at an elementary school in the south Jakarta area. The Example and Non-Example models can improve students' critical thinking because they have fun methods, students can be more active in class and exchange opinions with each other.